¿A right that is not a right? Right as political structure of disagreement - Quintana Porras, Laura (2018)
By studying discursive productions in certain popular movements, I would like to examine in this text the way in which these movements vindicate, in their transformative practices, a right that cannot be reduced to the instituted rights in a legal sense, nor interpreted in accordance with a merely reformist comprehension of political action. I thus seek to define a “right that is not a right”. This right is essential in showing how these actions can be the site of processes of political subjectivation from which there can emerge both polemical instances of disidentification and other forms of being-together that could be considered simultaneously dissensual and “experimental”.